Adaptive Liquid Interfacially Assembled Protein Nanosheets for Guiding Mesenchymal Stem Cell Fate. Issue 4 (9th December 2019) - Jia, Xiaofang; Minami, Kosuke; Uto, Koichiro; Chang, Alice Chinghsuan; Hill, Jonathan P.; Nakanishi, Jun; Ariga, Katsuhiko
Abstract: There is a growing interest in the development of dynamic adaptive biomaterials for regulation of cellular functions. However, existing materials are limited to two‐state switching of the presentation and removal of cell‐adhesive bioactive motifs that cannot emulate the native extracellular matrix (ECM) in vivo with continuously adjustable characteristics. Here, tunable adaptive materials composed of a protein monolayer assembled at a liquid–liquid interface are demonstrated, which adapt dynamically to cell traction forces. An ultrastructure transition from protein monolayer to hierarchical fiber occurs through interfacial jamming. Elongated fibronectin fibers promote formation of elongated focal adhesion structures, increase focal adhesion kinase activation, and enhance neuronal differentiation of stem cells. Cell traction force results in spatial rearrangement of ECM proteins, which feeds back to alter stem cell fate. The reported biomimetic adaptive liquid interface enables dynamic control of stem cell behavior and has potential translational applications. Abstract : An adaptive dynamic system is engineered from a protein monolayer assembled at the water–perfluorocarbon interface. The soft liquid interface, which adapts dynamically to cell‐generated forces, guides differentiation of stem cells, and has broad implications for tissue engineering and regenerative medicine applications.